1986
DOI: 10.1128/iai.53.2.411-419.1986
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a secretory proteinase of Candida parapsilosis and evidence for the absence of the enzyme during infection in vitro

Abstract: The opportunistic yeastlike fungi of the genus Candida comprise three species which are proteolytic in vitro. Among them, C. albicans and C. tropicalis are of foremost medical importance. However, a strict correlation between extracellular proteolytic activity and virulence is opposed by the low virulence of the third proteolytic species, C. parapsilosis. We purified the secretory acid proteinase of C. parapsilosis (clinical isolate 265). The enzyme is a carboxyl proteinase (EC 3.4.23) like all other secretory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(27 citation statements)
references
References 34 publications
2
24
0
1
Order By: Relevance
“…Once adhered to surfaces in the oral cavity, Candida cells may invade tissues. This process has been linked to the ability of C. albicans strains to produce hyphae and proteinase (11,28,32,43), and the data in the current study agree with these findings. Other investigators (30) have demonstrated that hyphae produce proteinases at their growing tips.…”
Section: Discussionsupporting
confidence: 90%
“…Once adhered to surfaces in the oral cavity, Candida cells may invade tissues. This process has been linked to the ability of C. albicans strains to produce hyphae and proteinase (11,28,32,43), and the data in the current study agree with these findings. Other investigators (30) have demonstrated that hyphae produce proteinases at their growing tips.…”
Section: Discussionsupporting
confidence: 90%
“…However, only one product has been identified as an extracellular aspartic protease. This protease has been partially characterized [29,30]. Fusek et al [31] isolated two aspartic proteases secreted by C. parapsilosis.…”
mentioning
confidence: 99%
“…are divergent. 31,32 Taken together, the development of broad Sap isoenzyme specific inhibitors is plausible and effective during different stages of infection, as well as lucrative. Sap-specific inhibition is also required to circumvent the involvement of endogenic proteinases.…”
Section: Discussionmentioning
confidence: 99%